2016
DOI: 10.20884/1.jm.2016.11.1.201
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolite from Endophytic Fungi Aspergillus Sp. The Leave Of Kunyit Putih (Curcuma zedoaria (Berg) Roscoe)

Abstract: The compound from endophytic fungi of Aspergillus sp. from leaves of kunyit putih (Curcuma zedoaria (Berg.) Roscoe) has been isolated. Isolation begins with cultivation ofAspergillus sp. in 18 L PDB’s media (Potato Dextrose Broth) for 28 days. The liquid cultivation medium was extracted by partitioning method using ethylacetate and then evaporated. The extract was separated and purified by chromatography techniques. Elucidation stucture of the isolated compound was analysis by spectroscopic method NMR 1D and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Senyawa antibakteri yang dihasilkan oleh jamur endofit juga dapat diproduksi dengan fermentasi cair atau submerged fermentation. Penelitian yang dilakukan oleh Muharni et al (2016); Pansanit & Pripdeevech (2018) dalam memproduksi senyawa antibakteri dari jamur endofit menggunakan medium cair berupa Potato Dextrose Broth (PDB). Isolat jamur endofit sebelum melalui proses fermentasi, dikulturkan kembali dengan menggunakan media agar seperti Potato Dextrose Agar dan diinkubasi pada suhu ruang selama 7 hari.…”
Section: Metode Isolasi Dan Karakterisasi Jamur Endofit Dari Tanaman Curcuma Dan Zingiberunclassified
See 2 more Smart Citations
“…Senyawa antibakteri yang dihasilkan oleh jamur endofit juga dapat diproduksi dengan fermentasi cair atau submerged fermentation. Penelitian yang dilakukan oleh Muharni et al (2016); Pansanit & Pripdeevech (2018) dalam memproduksi senyawa antibakteri dari jamur endofit menggunakan medium cair berupa Potato Dextrose Broth (PDB). Isolat jamur endofit sebelum melalui proses fermentasi, dikulturkan kembali dengan menggunakan media agar seperti Potato Dextrose Agar dan diinkubasi pada suhu ruang selama 7 hari.…”
Section: Metode Isolasi Dan Karakterisasi Jamur Endofit Dari Tanaman Curcuma Dan Zingiberunclassified
“…Penelitian serupa juga pernah dilakukan oleh Muharni et al (2016) yang menemukan Aspergillus sp. sebagai kapang endofit pada tanaman kunyit putih (C. zedoaria) tersebut.…”
Section: Efektivitas Antibakteri Yang Dihasilkan Oleh Jamur Endofit Dari Tanaman Marga Curcuma Dan Zingiberunclassified
See 1 more Smart Citation
“…The results showed that the miana leaf extract with high concentrations resulted in a wider inhibition zone than those with low concentrations [19]. Another study on miana leaves found that the ethanol extract of Coleus scutellarioides Linn has antibacterial activity on E. coli and S. aureus bacteria [23]. The dissertation by Palette Tandi found that purple miana leaf extract has a pharmacotherapy effect for mycobacterium tuberculosis infection [22].…”
Section: A Inhibitory Power Of Miana Leaf Extract On the Growth Of E Coli Bacteria With Extract Concentrations Of 15% 30% 50% And 90%mentioning
confidence: 99%
“…Observations on the diameter of the clear zone around the paper disc indicated as an inhibitory reaction of the rhizobacteria against Xoo bacteria, and each test was performed four times. Antibiosis activity of supernatant was performed using paper disc diffusion method (Muharni et al 2016;Rahma et al 2018). Four biocontrols standard and rice growth promoter rhizobacterial isolates were used as positive control.…”
Section: Antibiosis Ability Testmentioning
confidence: 99%